2019
DOI: 10.1017/ice.2019.253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multifaceted approach to antimicrobial stewardship education methods for medical residents

Abstract: Objective:Medical residents are an important group for antimicrobial stewardship programs (ASPs) to target with interventions aimed at improving antibiotic prescribing. In this study, we compared antimicrobial prescribing practices of 2 academic medical teams receiving different ASP training approaches along with a hospitalist control group.Design:Retrospective cohort study comparing guideline-concordant antibiotic prescribing for 3 common infections among a family medicine (FM) resident service, an internal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This study also adds to the growing body of evidence showing the importance of ASP interventions involving physician residents to establish good prescribing habits early in practice. 15,17,18 Furthermore, these results support the finding that syndrome-specific interventions are successful in improving antibiotic prescribing in the outpatient setting. 19 Previous studies evaluating multifaceted approaches to implementing ASPs in outpatient settings have also demonstrated success when targeting syndrome-specific prescribing by combining educational interventions with EHR optimization and peer-to-peer comparison.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This study also adds to the growing body of evidence showing the importance of ASP interventions involving physician residents to establish good prescribing habits early in practice. 15,17,18 Furthermore, these results support the finding that syndrome-specific interventions are successful in improving antibiotic prescribing in the outpatient setting. 19 Previous studies evaluating multifaceted approaches to implementing ASPs in outpatient settings have also demonstrated success when targeting syndrome-specific prescribing by combining educational interventions with EHR optimization and peer-to-peer comparison.…”
Section: Discussionsupporting
confidence: 65%
“…[7][8][9][10][11][12] Furthermore, few efforts have targeted medical residents, an important target for ASPs in establishing good habits for antibiotic prescribing. [13][14][15] Although infectious diseases (ID) practitioners typically serve as ASP leaders in inpatient settings, this resource may be scarce in the outpatient setting. Ambulatory care pharmacists (AMCPs) working within primary-care practice sites may serve a critical role as stewardship collaborators and leaders in the outpatient setting; they have established relationships with the provider team and skills needed to identify problematic trends in antimicrobial use and to provide active intervention.…”
mentioning
confidence: 99%
“…The participation of the pharmacist within the health care team translates into a decrease in unnecessary costs, an increase in the quality of care and an improvement in the patient's quality of life. These results have led to the acceptance of this professional by other members of the health team [36][37][38][39][40][41]. To date, there is no clinical pharmacist at the target institution involved in the design, implementation and review of therapeutic protocols, including PAP.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies included inpatients and reported an average length of antibiotic treatment of 5-17 days. 40,46,48,49,[52][53][54]57,58 Clinical response rates were all above 85%, failure rates ranged from 5-12% and recurrence rates from 0-17%. Eleven studies, including those treated as outpatients/OPAT, reported an average length of IV therapy of 2-7 days and an average overall treatment duration of 6-10 days.…”
Section: Evidence For Overall Duration Of Therapymentioning
confidence: 94%